MANAJEMEN KINERJA PEGAWAI PADA PELAYANAN AKTA KELAHIRAN - Abd. Rohman; Vincentia Sinka Tiara; Dominika Dewiyanti (Unitri Press, 2021)
This study’s purpose was analyzing employee performance management in providing services to the community. The research method used was descriptive qualitative with technical data analysis using Miles, Huberman, and Saldana models. The results of the study indicated that employee performance management in the Birth Certificate service is carried out by producing a Birth Certificate that is in accordance with the truth of the data elements in the application file (on requirements) and the Population database. The Village Head/Village Secretary also always corrects the work of his employees before signing the file. The process of completing the Birth Certificate is also carried out very quickly so that people do not have to wait too long. The village government uses two methods, namely the manual method and online-based. This manual method is carried out if the process of issuing a Birth Certificate cannot be carried out through SIMADE. While this online-based service is carried out through SIMADE (Village Management Information System). SIMADE is an information system that can accommodate most administrative service activities at the Village office more quickly and accurately to help village officials to improve their performance in providing services